Stem Cell Therapy: A Promising Therapeutic Method for Intracerebral Hemorrhage - Liansheng Gao (Cell Transplantation, 2018)
Spontaneous intracerebral hemorrhage (ICH) is one type of the most devastating cerebrovascular diseases worldwide, which causes high morbidity and mortality. However, efficient treatment is still lacking. Stem cell therapy has shown good neuroprotective and neurorestorative effect in ICH and is a promising treatment. In this study, our aim was to review the therapeutic effects, strategies, related mechanisms and safety issues of various types of stem cell for ICH treatment. Numerous studies had demonstrated the therapeutic effects of diverse stem cell types in ICH. The potential mechanisms include tissue repair and replacement, neurotrophy, promotion of neurogenesis and angiogenesis, anti-apoptosis, immunoregulation and anti-inflammation and so forth. The microenvironment of the central nervous system (CNS) can also influence the effects of stem cell therapy. The detailed therapeutic strategies for ICH treatment such as cell type, the number of cells, time window, and the routes of medication delivery, varied greatly among different studies and had not been determined. Moreover, the safety issues of stem cell therapy for ICH should not be ignored. Stem cell therapy showed good therapeutic effect in ICH, making it a promising treatment. However, safety should be carefully evaluated, and more clinical trials are required before stem cell therapy can be extensively applied to clinical use.